Prevalence and characteristics of women with borderline personality pathology referred to a perinatal consultation liaison service. (September 2021) - Nagel, Katharina; Thomson, Richard; Lorimer, Stephanie; Judd, Fiona
Objective: To examine the prevalence and characteristics of pregnant women with borderline personality pathology (defined as borderline personality disorder and borderline personality traits) referred to a perinatal consultation-liaison psychiatry service. Method: Socio-demographic and clinical data, and diagnoses made according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria were recorded for all women referred to and seen by the perinatal consultation-liaison psychiatry service over an 18-month period. Data were analysed using descriptive statistics and logistic regression analysis. Results: A total of 318 women were seen. The most common diagnoses found were depressive disorder (25.5%) and anxiety disorder (15.1%). Borderline personality disorder was found in 10.1% of women and almost one in five women had two or more borderline personality traits (19.5%). When compared to women with other diagnoses, women with borderline personality pathology had higher rates of unplanned pregnancy, being unpartnered, substance use during pregnancy and higher rates of child safety services involvement as a child or in a previous pregnancy. Over 40% of women with borderline personality pathology were referred to child safety services in the current pregnancy and a diagnosis of borderline personality pathology increased the risk of child safety services involvement by almost sixfold (odds ratio: 5.5; 95% confidence interval = [1.50, 20.17]). Conclusion: The prevalence of borderline personality pathology in antenatal women identified at antenatal screening and the recognition that women with borderline personality pathology are 'high-risk' caregivers argue for borderline personality pathology to be recognised as a high priority for investment in service development.